2017
DOI: 10.1113/jp274404
|View full text |Cite
|
Sign up to set email alerts
|

The mechanosensitive Piezo1 channel: structural features and molecular bases underlying its ion permeation and mechanotransduction

Abstract: The evolutionarily conserved Piezo family of proteins, including Piezo1 and Piezo2, encodes the long-sought-after mammalian mechanosensitive cation channels that play critical roles in various mechanotransduction processes such as touch, pain, proprioception, vascular development and blood pressure regulation. Mammalian Piezo proteins contain over 2500 amino acids with numerous predicted transmembrane segments, and do not bear sequence homology with any known class of ion channels. Thus, it is imperative, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 63 publications
0
52
0
Order By: Relevance
“…Piezo channels have been demonstrated to play critical roles in various mechanotransduction processes via characterizing Piezo1 or Piezo2 knockout mice . For example, Piezo1 expressed in endothelial cells is critical for sensing blood flow‐associated shear stress for proper blood vessel development and blood pressure regulation , while Piezo2 expressed in primary sensory neurons mediates the sensation of gentle touch , proprioception , airway stretch, and lung inflation .…”
Section: Introductionmentioning
confidence: 99%
“…Piezo channels have been demonstrated to play critical roles in various mechanotransduction processes via characterizing Piezo1 or Piezo2 knockout mice . For example, Piezo1 expressed in endothelial cells is critical for sensing blood flow‐associated shear stress for proper blood vessel development and blood pressure regulation , while Piezo2 expressed in primary sensory neurons mediates the sensation of gentle touch , proprioception , airway stretch, and lung inflation .…”
Section: Introductionmentioning
confidence: 99%
“…54 Membrane tension highly regulates Piezo1, a cytoskeleton-independent Ca 2+ -permeable nonselective cation channel, 55,56 which response to mechanical loading 57 within milliseconds. 18 Furthermore, Piezo1 is known to regulate the mechanotransductive release of ATP into the extracellular environment. 16,17 Piezo1 possesses a self-regulatory gating mechanism at the globular C-terminal extracellular domain, which is crucial for frequency filtering of repetitive mechanical stimuli 58 and loading intensity.…”
Section: Discussionmentioning
confidence: 99%
“…15 Piezo1 channels are located in the membrane bilayer and respond shear stress-induced membrane stretch within milliseconds after mechanical loading, independent of the cytoskeleton, leading to the release of adenosine triphosphate (ATP) in the extracellular environment. [16][17][18] A recent study found that co-localization of sarcoplasmic/endoplasmic Ca 2+ reticulum ATPase 2 (SERCA2) with Piezo1 suppresses mechanosensitivity of Piezo1. 19 However, it is unknown how activation of Piezo1 and co-localization of Piezo1with SERCA2 are governed by fluid flow with different dynamic properties, and whether activation of these molecules is related to the stimulation of osteoclast formation.…”
Section: Introductionmentioning
confidence: 99%
“…Here we present a review series associated with our ‘Piezo channel mechanisms and disease’ symposium at the International Union of Physiological Sciences (IUPS) congress in Rio de Janeiro on 3 August 2017. The series focuses on three key topics from the symposium: Piezo1 channel structure (Wang & Xiao, ), Piezo1 in vascular physiology (Beech, ) and Piezo1 in genetic disease (Martin‐Almedina et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…). The structure article reviews the breakthrough in determining the tri‐blade propeller‐like arrangement of Piezo1 channels and discusses the hypothesis that the channels comprise discrete mechano‐transduction and ion‐conducting modules which coordinate to fulfil the overall purpose of the channels (Wang & Xiao, ). The physiology article reviews current knowledge of the role of Piezo1 channels in the endothelium, discussing the hypothesis that the channels are key sensors of the frictional force of blood flow, leading them to be essential in vascular development and necessary for redistribution of blood flow in exercise and optimal physical performance (Beech, ).…”
Section: Introductionmentioning
confidence: 99%